2015
DOI: 10.1111/apha.12531
|View full text |Cite
|
Sign up to set email alerts
|

The giraffe kidney tolerates high arterial blood pressure by high renal interstitial pressure and low glomerular filtration rate

Abstract: In giraffes, GFR, ERPF and RI appear much lower than expected based on body mass. A strong renal capsule supports a RIHP, which is >10-fold that of other mammals effectively reducing the net filtration pressure and protecting against the high MAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Their heart valves have evolved to adapt to an extreme‐pressure system with compact collagen construction . A strong renal capsule supporting high renal interstitial hydrostatic pressure reduces the net filtration pressure and may protect giraffe kidneys against high blood pressure . The protective mechanisms in giraffes provide a conjectural framework for experimental explorations into mechanisms as well as treatment and prevention of hypertension, cardiovascular and renal disease in humans.…”
Section: Physiological Magicians In the Animal Kingdom – Implicationsmentioning
confidence: 99%
“…Their heart valves have evolved to adapt to an extreme‐pressure system with compact collagen construction . A strong renal capsule supporting high renal interstitial hydrostatic pressure reduces the net filtration pressure and may protect giraffe kidneys against high blood pressure . The protective mechanisms in giraffes provide a conjectural framework for experimental explorations into mechanisms as well as treatment and prevention of hypertension, cardiovascular and renal disease in humans.…”
Section: Physiological Magicians In the Animal Kingdom – Implicationsmentioning
confidence: 99%
“…The investigation of giraffes is not typical; however very interesting, since due to the exceptional geometry of the animal we find unique pressure conditions and alterations, for example for the brain, when the giraffe drinks water. The mean arterial blood pressure is twice that of other mammals . The authors analysed possible evolutionary adaption in kidney physiology in response to this high value of mean arterial pressure as compared with other mammals.…”
mentioning
confidence: 99%
“…The mean arterial blood pressure is twice that of other mammals. 15 The authors analysed possible evolutionary adaption in kidney physiology in response to this high value of mean arterial pressure as compared with other mammals. They have found that in giraffes the glomerular filtration rate, effective renal plasma flow and renal artery resistive index are much lower than expected based on body mass of the giraffes.…”
mentioning
confidence: 99%
“…Renal physiology and the pathophysiology of renal disease is a common topic in Acta Physiologica: Given the sharp increase in morbidity and mortality from kidney failure in many Western economies during the last century, understanding the mechanisms of normal kidney function, renal pathophysiology and the development of kidney failure and potential regenerative mechanisms is highly relevant.…”
mentioning
confidence: 99%